Multimodal imaging findings of primary liver clear cell carcinoma: a case presentation - Hu, Xianwen; Li, Xiaotian; Zhao, Wei; Cai, Jiong; Wang, Pan (Frontiers in Medicine, 2024)
Primary clear cell carcinoma of liver (PCCCL) is a special and relatively rare subtype of hepatocellular carcinoma (HCC), which is more common in people over 50 years of age, with a preference for men and a history of hepatitis B or C and/or cirrhosis. Herein, we present a case of a 60-year-old woman who came to our hospital for medical help with right upper abdominal pain. The imaging examination showed a low-density mass in the right lobe of his liver. In contrast enhanced computed tomography (CT) or T1-weighted imaging, significant enhancement can appear around the tumor during the arterial phase, and over time, the degree of enhancement of the tumor gradually decreases. The lession showed obviously increased fluorine-18 fluorodeoxyglucose ( 18 F-FDG) uptake on positron emission tomography/CT. These imaging findings contribute to the diagnosis of PCCCL and differentiate it from other types of liver tumors.